2017
DOI: 10.1515/intag-2016-0077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starch binder on charcoal briquette properties

Abstract: A b s t r a c t. The paper shows the results of a study on the effect of starch binder on the mechanical, physical and burning properties of charcoal briquettes. Two types of binders were repeatedly used to make briquettes of native wheat starch and modified wheat starch, at 8% of the whole. Briquetting was performed in a roller press unit, and pillow-shaped briquettes were made. The moisture of the mixed material ranged from 28 to 32%. The product, whether the former or the latter, was characterized by very g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 8 publications
2
21
1
1
Order By: Relevance
“…These results can be likened to the best shatter indices (98.21% and 98.17%) obtained for sawdust and charcoal briquettes in Ajiboye et al [81]. According to Borowski et al [82], the shatter index of briquettes should be at least 90%. In a previous study, a minimum value of 50% was considered an acceptable shatter index for fuel briquettes developed for industrial and domestic applications [80].…”
Section: Shatter Indexsupporting
confidence: 55%
“…These results can be likened to the best shatter indices (98.21% and 98.17%) obtained for sawdust and charcoal briquettes in Ajiboye et al [81]. According to Borowski et al [82], the shatter index of briquettes should be at least 90%. In a previous study, a minimum value of 50% was considered an acceptable shatter index for fuel briquettes developed for industrial and domestic applications [80].…”
Section: Shatter Indexsupporting
confidence: 55%
“…The tests conducted in order to determine the mechanical properties of coal briquettes were also performed by using a testing machine (capacity of 10 kN) to conduct axial compression test until the structure of coal briquette failed. According to Borowski et al (2017) study, the minimum compressive strength value should be above 1.0 MPa.…”
Section: Methodsmentioning
confidence: 99%
“…The compressive strengths of coal briquettes of peanut shells and cashew shells are below 1 MPa. According to the study of Borowski et al (2017), these briquettes are not suitable for transport and storage. Porosity plays a crucial role in the exchange of water (water uptake) during the absorption or desorption cycles depending on the storage medium (effect of relative humidity).…”
Section: Physical and Mechanical Properties Of Coal Briquettesmentioning
confidence: 99%
“…Charcoal pellets with arabic gum had the better compressive strength compared to those produced with wheat starch. According to the study of Borowski, et al [8], the minimum compressive strength value, for briquettes with better quality, should be above 1.0 MPa. Ramaroson, et al [9] found compressive strength of 1.25 MPa with coal briquettes made of 6% cassava starch and compaction pressure equal to 39.8 MPa.…”
Section: Axial Compressive Strengthmentioning
confidence: 99%